Challenges of EBVM as a RVN in a Practice Setting - O’Dwyer, Louise (Veterinary Evidence, 2017)
This talk will look at difficulties for RVNs working in private practice gaining access to sufficient papers and studies in order to provide the evidence we need, and also looking at the selection of appropriate topics. We will look at sources of information such as the RCVS Knowledge library in order to collect evidence, and also how to select appropriate, relevant topics for research which will be useful to other RVNs working in practice, and will help in the creation of nursing protocols and nursing care bundles, which will advance nursing and patient care. This is a podcast of Louise’s talk at the Veterinary Evidence Today conference, Edinburgh November 1, 2016.